Understanding bullying experiences and student well-being in rural primary schools - Evana Rizqoh; Sriyanto (Indonesian Journal of Educational Development (IJED), 2026)
Bullying remains a recurring challenge within school environments, shaping children's emotional and academic well-being in complex ways. In Indonesia, particularly in rural primary school contexts, limited research has examined how children themselves interpret and make sense of their bullying experiences. This study aims to explore the forms of bullying experienced by rural primary school students and to examine how these experiences influence their emotional and academic well-being. Adopting a qualitative phenomenological design, this study involved six children aged 10–12 years who had experienced bullying in rural primary schools. Data were generated through semi-structured interviews with children, supported by interviews with teachers and parents, as well as classroom and playground observations. The data were analyzed using Interpretative Phenomenological Analysis (IPA). The findings indicate that bullying is experienced through verbal, physical, and social practices embedded in everyday peer interactions. These experiences negatively affect children's emotional well-being, manifested in fear, anxiety, emotional suppression, and social withdrawal, and undermine academic well-being through reduced motivation, concentration, and self-confidence. Supportive relationships with teachers, parents, and peers emerged as important protective factors that helped children sustain emotional stability and engagement in learning. This study highlights the importance of developing context-sensitive and supportive interventions to address bullying and promote student well-being in rural primary school settings.